The morphological pathogenesis of isolated superior mesenteric artery dissection - Hou, Li; Yin, Keli; Xiong, Jiang; Weng, Chengxin; Wang, Jiarong; Qi, Yuhan; Zheng, Tinghui; Wang, Tiehao; Yuan, Ding (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIsolated superior mesenteric artery dissection (ISMAD) is a rare arterial disease, and its exact cause is still not well understood. This study aimed to investigate the potential role of anatomical factors in the development of ISMAD.MethodsThis case-control study included patients diagnosed with ISMAD via computed tomography angiography from two major medical centers in China. An equal number of age-sex and body mass index matched patients without aortic and superior mesenteric artery disease were selected as controls. Several anatomical parameters were compared between the ISMAD group and the control group. Significant parameters were identified through univariate and multivariate analyses, and models were evaluated using receiver operating characteristic (ROC) curve analysis. A p-value < 0.05 was considered statistically significant.ResultsA total of 60 patients with isolated superior mesenteric artery dissection and 60 age-sex (52.6 ± 6.1 vs. 52.2 ± 13.5, p = 0.82) and body mass index (24.3 ± 2.5 vs. 24.0 ± 4.0, p = 0.72) matched normal controls from two major hospitals in China were included in the study. Compared with normal controls, the multivariate analysis revealed that curvature (OR 1.239, 95% CI 1.122–1.369, p < 0.001) and tortuosity (OR 0.002, 95% CI, 0.000–0.083, p = 0.001) were independent predictors of ISMAD occurrence.ConclusionPatients with ISMAD exhibited higher levels of curvature and lower levels of tortuosity compared to normal control group.